PENDAMPINGAN PEMBUATAN BUKU AJAR BER-ISBN UNTUK GURU MADRASAH IBTIDAIYAH DEMI MEMBANGUN KUALITAS PENDIDIKAN - Latifah, Eny; Afiyati, Roviqo; Roisyatul Hifdiyah, Wilda; Maulidah Putri, Gita Mei; Nur Amelia, Rika; Irawati, Henik (Jurnal Pengabdian Masyarakat Sabangka, 2025)
The quality of education at the elementary level, particularly in Islamic Elementary Schools (MI), is largely determined by the availability of relevant, contextual, and up-to-date learning resources. Textbooks are a crucial tool for supporting successful learning. However, limited teacher and educator skills in writing and publishing textbooks that meet national standards remain a challenge. This article aims to outline the importance of textbook development training and ISBN-based book publishing assistance as a strategy to improve the quality of education in Islamic Elementary Schools (MI). Using the Participatory Action Research (PAR) method, this article outlines the role of textbooks, the urgency of ISBN-based book publishing assistance, and their impact on improving teacher competency, student literacy interests, and the identity of educational institutions. The study findings demonstrate that these training and assistance significantly contribute to building a culture of literacy, enhancing teacher professionalism, and enriching teaching materials to meet the needs of madrasas.